Serum creatinine to cystatin C ratio predicts skeletal muscle mass and strength in patients with non-dialysis chronic kidney disease. Issue 8 (August 2020) - Lin, Yu-Li; Chen, Shu-Yuan; Lai, Yu-Hsien; Wang, Chih-Hsien; Kuo, Chiu-Huang; Liou, Hung-Hsiang; Hsu, Bang-Gee
Summary: Background & aims: Muscle wasting is highly prevalent in patients with chronic kidney disease (CKD). However, the assessment of skeletal muscle mass and strength in clinical settings is not commonly available. We aimed to evaluate the feasibility of serum creatinine/cystatin C (Cr/CysC) ratio in the assessment of muscle wasting. Methods: In 272 patients with CKD aged 66.5 ± 15.1 years, skeletal muscle mass and handgrip strength (HGS) were assessed. Skeletal muscle index (SMI) was calculated as skeletal muscle mass/height 2 . Low muscle mass was defined as SMI below the sex-specific 10th percentile of study population and low handgrip strength as less than 26 Kg for men and 18 Kg for women. Results: The Cr/CysC ratio was significantly lower in both the low SMI and low HGS groups. Moreover, the Cr/CysC ratio correlated with SMI (r = .306, p  < .001) and HGS (r = .341, p  < .001). After adjusting for confounding factors, age, sex, waist circumference, body fat mass, and Cr/CysC ratio were independently associated with SMI, whereas age, sex, diabetes, hemoglobin, estimated glomerular filtration rate, urine protein/creatinine ratio, SMI, and Cr/CysC ratio were independently associated with HGS. Conclusions: Cr/CysC ratio appears to be a promising surrogate marker for detecting muscle wasting in patients with CKD. Further studies are needed to extend our findings.